2021
DOI: 10.1016/j.eprac.2021.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D and Its Potential Benefit for the COVID-19 Pandemic

Abstract: Vitamin D is known not only for its importance for bone health, but also for its biologic activities on other many other organ systems. This is due to the presence of the vitamin D receptor (VDR) in various types of cells and tissues, including the skin, skeletal muscle, adipose tissue, endocrine pancreas, immune cells and blood vessels. Experimental studies have shown that vitamin D exerts several actions that are thought to be protective against COVID-19 infectivity and severity. These include the immunomodu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
72
0
9

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(82 citation statements)
references
References 119 publications
1
72
0
9
Order By: Relevance
“…Vitamin D has been proposed to be protective against COVID-19 infectivity and severity as it modulates the immune system by suppressing T helper 1 immune profile and upregulating the regulatory T cell expression, thereby reducing the severity of cytokine storm. [49][50][51][52] Therefore, Black patients may be at higher risk than White patients of cytokine storm and resulting systemic and intrarenal inflammation. This is also supported by the higher levels of inflammatory markers among Black patients observed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D has been proposed to be protective against COVID-19 infectivity and severity as it modulates the immune system by suppressing T helper 1 immune profile and upregulating the regulatory T cell expression, thereby reducing the severity of cytokine storm. [49][50][51][52] Therefore, Black patients may be at higher risk than White patients of cytokine storm and resulting systemic and intrarenal inflammation. This is also supported by the higher levels of inflammatory markers among Black patients observed in our study.…”
Section: Discussionmentioning
confidence: 99%
“…A meta‐analysis of 27 studies found that vitamin D insufficiency among patients with Covid‐19 was significantly associated with higher risks of severe infection, hospitalization, and mortality. 19 At the time of writing, there are several ongoing clinical trials aiming to identify a possible benefit of vitamin D supplementation on hospitalized patient outcomes in Covid‐19. However, the use of dexamethasone is likely to mitigate the identification of any signals due to vitamin D on inpatient outcomes such as respiratory failure.…”
Section: Discussionmentioning
confidence: 99%
“…1,25(OH)2D3 hücre içerisindeki işlevini reseptörüne bağlanarak göstermektedir (1). Vitamin D reseptörleri bağışıklık hücreleri, deri, iskelet kası dahil çeşitli hücre ve doku türlerinde yaygın olarak bulunmaktadır (6). D vitamininin immün sistem de dahil olmak üzere bir çok vücut sisteminde rolü olduğu tespit edilmiştir (1).…”
Section: Vitamin Dunclassified
“…D vitamininin immün sistem de dahil olmak üzere bir çok vücut sisteminde rolü olduğu tespit edilmiştir (1). Hem doğal, hem de edinsel bağışıklık sistemini düzenleyen immünomodülatör bir ajan olarak kabul edilmektedir (6). Zarflı ve zarfsız virüslere karşı doğrudan antimikrobiyal etki gösteren defensin, katelisidin gibi peptidlerin ekspresyonunu arttırarak doğal hücresel immün yanıtı arttırır.…”
Section: Vitamin Dunclassified
See 1 more Smart Citation